2019
DOI: 10.1002/cpmc.92
|View full text |Cite
|
Sign up to set email alerts
|

Rift Valley Fever Virus: Propagation, Quantification, and Storage

Abstract: Rift Valley fever virus (RVFV) is an arthropod‐borne, zoonotic disease endemic to sub‐Saharan Africa and the Arabian Peninsula. Outbreaks of Rift Valley fever have had up to 100% mortality rates in fetal and neonatal sheep. Upon infection of ruminant and human hosts alike, RVFV infection causes an at times severe hepatitis and pathology in many other organs. The enveloped virion contains a tripartite, predominantly negative‐sense, single‐stranded RNA genome, which codes for the proteins the virus needs to repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Although phylogenetic analysis indicates that HEDV and RVFV have an evolutionary relationship, there are marked differences in the infectivity of the two viruses for tissue culture cells. RVFV causes CPE in a variety of tissue culture cells, including BHK-21, Vero, and Vero-E6 cells [ 27 ]. Although it did not cause significant CPE in mosquito C6/36 cells, C6/36 cells amplified RVFV [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although phylogenetic analysis indicates that HEDV and RVFV have an evolutionary relationship, there are marked differences in the infectivity of the two viruses for tissue culture cells. RVFV causes CPE in a variety of tissue culture cells, including BHK-21, Vero, and Vero-E6 cells [ 27 ]. Although it did not cause significant CPE in mosquito C6/36 cells, C6/36 cells amplified RVFV [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Viral titers, expressed as TCID50/mL, were calculated according to both Reed and Muench and Karber methods based on eight replicates for dilution, as previously de-scribed [30][31][32]. 10 −6 and 10 −7 dilutions could not be successfully titrated because of a lack of data.…”
Section: Viral Titrationmentioning
confidence: 99%
“…To establish and validate the assay, we needed to identify an appropriate cell line, define primary antibodies capable of detecting viral antigen, and determine an optimal cell concentration. Previous work from a number of laboratories demonstrated that Vero E6 cells, a non-human primate African green monkey kidney epithelial cell line, was highly sensitive to RVFV infection and are widely available [38].…”
Section: Resultsmentioning
confidence: 99%